Vortex solutions in the noncommutative torus - Lozano, G.S. (2006)
Vortex configurations in the two-dimensional torus are considered in noncommutative space. We analyze the BPS equations of the Abelian Higgs model. Numerical solutions are constructed for the self-dual and anti-self dual cases by extending an algorithm originally developed for ordinary commutative space. We work within the Fock space approach to noncommutative theories and the Moyal-Weyl connection is used in the final stage to express the solutions in configuration space. © SISSA 2006.